Increased nuchal translucency is associated with jugular lymphatic distension. - Haak, M; Bartelings, M; Jackson, D; Webb, S; van Vugt, J; Gittenberger-de Groot, A (2002)
BACKGROUND: Measurement of nuchal translucency (NT) is a widely used method of screening for chromosomal abnormalities. Increased NT is seen in a diversity of fetal malformations. The mechanism explaining the abnormal fluid accumulation and the transient nature of NT remains unexplained. METHODS: The nuchal regions of normal and trisomy 16 mouse embryos were examined for (lympho)vascular abnormalities using immunohistochemical markers against lymphatic vessels (LYVE-1) and smooth muscle (1A4) and endothelial (CD34) cells. Additionally, an ultrasonographic study was carried out on 17 human fetuses with an increased NT. Two of these fetuses were examined morphologically. RESULTS: In both abnormal human and mouse specimens, we found a mesenchyme lined cavity within the posterior nuchal region as well as bilaterally enlarged jugular LYVE-1 positive lymphatic sacs. The persistence of jugular lymphatic sacs was also confirmed by ultrasound in 14 human fetuses with increased NT. CONCLUSION: Our findings identify the cause of increased NT as mesenchymal oedema in the presence of distended jugular lymphatic sacs, detected by the hyaluronan receptor LYVE-1. The delayed organization and connection of these lymphatic sacs to the venous circulation might explain the transient nature of NT. Disturbance in timing of endothelial differentiation might be a common denominator in the origin of NT, linking cardiovascular and haemodynamic abnormalities.